2019
DOI: 10.3390/nu11030648
|View full text |Cite
|
Sign up to set email alerts
|

Hesperetin, a Citrus Flavonoid, Attenuates LPS-Induced Neuroinflammation, Apoptosis and Memory Impairments by Modulating TLR4/NF-κB Signaling

Abstract: Glial activation and neuroinflammation play significant roles in apoptosis as well as in the development of cognitive and memory deficits. Neuroinflammation is also a critical feature in the pathogenesis of neurodegenerative disorders such as Alzheimer and Parkinson’s diseases. Previously, hesperetin has been shown to be an effective antioxidant and anti-inflammatory agent. In the present study, in vivo and in vitro analyses were performed to evaluate the neuroprotective effects of hesperetin in lipopolysaccha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
238
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 352 publications
(249 citation statements)
references
References 71 publications
9
238
0
2
Order By: Relevance
“…Reduced circulating APN levels have been observed in aged obese individuals and obese patients with type 2 diabetes mellitus [77,78]. Importantly, chronic APN deficiency due to AMPK inactivation causes cerebral insulin resistance in mice, i.e., increases IRS-1 phosphorylation at serine 616 and inhibits the formation of pIRS-1Tyr in neurons, leading AD-like pathologies [46]. Similarly, impaired brain insulin signaling is also associated with pro-inflammatory signaling: abnormal serine phosphorylation of IRS-1 (IRS-1pSer636) is caused by TNF-α activation via the JNK/TNF-α pathway and is blocked by infliximab, a TNF-α neutralizing antibody [79].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Reduced circulating APN levels have been observed in aged obese individuals and obese patients with type 2 diabetes mellitus [77,78]. Importantly, chronic APN deficiency due to AMPK inactivation causes cerebral insulin resistance in mice, i.e., increases IRS-1 phosphorylation at serine 616 and inhibits the formation of pIRS-1Tyr in neurons, leading AD-like pathologies [46]. Similarly, impaired brain insulin signaling is also associated with pro-inflammatory signaling: abnormal serine phosphorylation of IRS-1 (IRS-1pSer636) is caused by TNF-α activation via the JNK/TNF-α pathway and is blocked by infliximab, a TNF-α neutralizing antibody [79].…”
Section: Discussionmentioning
confidence: 99%
“…Lipid peroxidation (LPO) quantification assays were conducted to assess oxidative stress [46]. Briefly, the levels of free malondialdehyde (MDA), a marker of LPO, in brain homogenates, as well as in the embryonic mouse hippocampal cell line mHippoE-14, were measured using a lipid peroxidation (MDA) colorimetric/fluorometric assay kit (Bio Vision, Milpitas, CA, USA, Cat #K739-100), according to the manufacturer's recommended protocol.…”
Section: Assessment Of Lipid Peroxidation (In Vivo and In Vitro)mentioning
confidence: 99%
“…it has previously been reported that alT promotes apoptosis in osteosarcoma (28)(29)(30); therefore, the effect of alT on the expression levels on Bcl-2, Bax, cleaved caspase-3 and cleaved caspase-8, which all serve important roles in the process of apoptosis was explored. The expression levels of cleaved caspase-3 and cleaved caspase-8 were significantly upregulated in the alT-treated u2oS cells compared with the untreated cells ( Fig.…”
Section: Inhibitory Mechanisms Of Alt In Osteosarcoma Cellsmentioning
confidence: 99%
“…Naturally derived compounds that inhibit the generation of proinflammatory cytokines could be alternative anti-inflammatory agents. Inhibitory effects of phytochemicals on the generation of proinflammatory cytokines have been extensively studied to develop anti-inflammatory agents to inhibit inflammatory diseases [2,4,25]. In this study, we demonstrated that myricetin remarkably inhibited the generation of TNF-α, IL-1β and PGE 2 in LPS-stimulated BV2 microglia.…”
Section: Discussionmentioning
confidence: 56%
“…Microglia are found in the central nervous system (CNS) where they play a pivotal role in the immune response and maintaining homeostasis in the brain, protecting the CNS against diverse types of pathogens. Infection, injury and irritants such as lipopolysaccharide (LPS) lead to the activation of microglia and the release of various cytokine and chemokine factors including cyclooxygenase-2 (COX-2) and inducible nitric oxide (NO) synthase (iNOS), inflammatory modulators such as prostaglandin E 2 (PGE 2 ) and NO, proinflammatory cytokines such as interleukin-1β (IL-1β) and tumor necrosis factor-α (TNF-α) [1][2][3][4]. These neuroinflammatory molecules secreted by activated microglia are reported to be associated with mitogen-activated protein kinase (MAPK), nuclear factor (NF)-κB signaling [2,5].…”
Section: Introductionmentioning
confidence: 99%